Effectiveness of MPO Recruitment and selection process of Square Pharmaceuticals Ltd. and Escalate efficiency. - Naoshin, Nuzhat (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.